Reinforcing Nano Finance Policy and an Alternative Approach to the Reduction on Social Inequality in Thailand - ชะมารัมย์, สุรศักดิ์ (Journal for Developing the Social and Community, 2016)
Social inequality, currently, has become another important issue in society that has been widely popular and discussed in every country throughout the world. It seems that the issue of social inequality will continue to be a structural problem in Thai society that has caused the majority of Thai people in the country to suffer. The government of General Prayut Chan-Ocha (year B.E. 2557-present) has recognized and appreciated the people’s needs to formulate Nano Finance under supervision which is believed to increase economic opportunities and to reduce long-term economic and social disparities. Thus, this article aims at explaining the division of Nano Finance under supervision and Impacts on the reduction of social inequality in Thailand. In addition, offering of policy recommendations on the driving of Nano Finance Policy more effectively. It is expected that this will be beneficial to the planning, developing, and improving of Nano Finance policy measures to be used as an alternative fiscal tool for successfully social inequality reducing in Thai society.